Standardization of a SYBR Green Based Real-Time PCR System for Detection and Molecular Quantification of Babesia bovis and B. bigemina in Water Buffaloes (Bubalus bubalis) - Obregón, Dasiel; Rabelo, Marcio D.; Giglioti, Rodrigo; Bilhassi, Thalita B.; Néo, Thalita A.; Corona, Belkis; Alfonso, Pastor; Machado, Rosangela Z.; Oliveira, Marcia C.S. (Journal of Buffalo Science, 2016)
Water buffalo (Bubalus bubalis) is a potential reservoir for Babesia bovis and B. bigemina in tropical regions, but the epidemiological evidence of their reservoir competence is limited, especially due to the lack of diagnostic tests capable of detecting and quantifying the low-level parasitemia present in the carrier animals. In this paper we present the standardization process of a SYBR Green based real-time PCR system (qPCR), consisting of two single qPCR assays, for the detection and quantification of B. bovis and/or B. bigemina. Both assays were optimized in similar protocols, including reagent concentrations and thermocycling parameters, so it is possible its use as a multiple qPCR in a single run. Both single assays showed a suitable analytical performance, especially by allowing detection of a greater number of carrier animals when compared with nested PCR assays (nPCR) against a reference panel of 60 DNA samples extracted from blood of both, infected- and non-infected buffaloes. Furthermore, a mathematical algorithm to convert the qPCR outcomes in percent of infected red blood cell was used, and was found that the estimated parasitemia in carrier buffaloes within the reference sample panels were close to those described in carrier cattle. This method could be a useful tool for epidemiological studies on the participation of the bubaline specie in the epidemic process of bovine babesiosis.